THE INFLUENCE OF SIMULATION MODEL ASSISTED BY FILM MEDIA ON THE ABILITY TO DEMONSTRATE DRAMA SCRIPTS OF GRADE XI STUDENTS AT SMA SWASTA PELITA PEMATANGSIANTAR - Marini, Netti; Turnip, Berlian. R.; Suprayogo, Budi; Garingging, Rasya Aprilia; Rahayu, Dina Sekar; Ningsih, Wahyu (Journal Analytica Islamica, 2025)
This study aims to examine the influence of a simulation learning model assisted by film media on the ability of Grade XI students at SMA Swasta Pelita Pematangsiantar to demonstrate drama scripts. The background of this research lies in the low level of student participation and skills in performing drama scripts, which is attributed to a lack of interest, inadequate training, and the use of inappropriate learning models. This research employs a quantitative approach using a quasi-experimental method with a pre-test and post-test design applied to two groups: an experimental group and a control group. The research instrument consists of essay tests, which were analyzed using normality tests, homogeneity tests, and paired sample t-tests through the SPSS application. The results show that the data are normally distributed and homogeneous, and there is a significant difference between the pre-test and post-test mean scores in the experimental group (from 66.93 to 82.80) compared to the control group (from 49.86 to 76.89). These findings indicate that the implementation of the simulation model assisted by film media is effective in improving students’ ability to perform drama scripts. Therefore, this model can be recommended as an alternative learning strategy to enhance students’ speaking skills and literary appreciation in an active, creative, and contextual manner.